Trends in Management of Fetuses with Suspected Lower Urinary Tract Obstruction (LUTO): A High-Risk Fetal and Pediatric Center Experience in a Universal-Access-to-Care System - Richter, Juliane; Doktor, Fabian; Good, Hayley; Erdman, Lauren; Kim, Jin K.; Santos, Joana Dos; Brownrigg, Natasha; Chua, Michael; Lorenzo, Armando J.; Rickard, Mandy; Mieghem, Tim Van; Shinar, Shiri (European Journal of Pediatric Surgery, 2023)
Introduction Neonates with lower urinary tract obstruction (LUTO) experience high morbidity and mortality associated with the development of chronic kidney disease. The prenatal detection rate for LUTO is less than 50%, with late or missed diagnosis leading to delayed management and long-term sequelae in the remainder. We aimed to explore the trends in prenatal detection and management at a high-risk fetal center and determine if similar trends of postnatal presentations were noted for the same period.Methods Prenatal and postnatal LUTO databases from a tertiary fetal center and its associated pediatric center between 2009 and 2021 were reviewed, capturing maternal age, gestational age (GA) at diagnosis, and rates of termination of pregnancy (TOP). Time series analysis using autocorrelation was performed to investigate time trend changes for prenatally suspected and postnatally confirmed LUTO cases.Results A total of 161 fetuses with prenatally suspected LUTO were identified, including 78 terminations. No significant time trend was found when evaluating the correlation between time periods, prenatal suspicion, and postnatal confirmation of LUTO cases (Durbin–Watson [DW] = 1.99, p = 0.3641 and DW = 2.86, p = 0.9113, respectively). GA at referral was 20.0 weeks (interquartile range [IQR] 12, 35) and 22.0 weeks (IQR 13, 37) for TOP and continued pregnancies (p < 0.0001). GA at initial ultrasound was earlier in terminated fetuses compared to continued (20.0 [IQR 12, 35] weeks vs. 22.5 [IQR 13, 39] weeks, p < 0.0001). While prenatal LUTO suspicion remained consistently higher than postnatal presentations, the rates of postnatal presentations and terminations remained stable during the study years (p = 0.7913 and 0.2338), as were GA at TOP and maternal age at diagnosis (p = 0.1710 and 0.1921).Conclusion This study demonstrated that more severe cases of LUTO are referred earlier and are more likely to undergo TOP. No significant trend was detected between time and prenatally suspected or postnatally confirmed LUTO, highlighting the need for further studies to better delineate factors that can increase prenatal detection.
Keywords: lower urinary tract obstruction (LUTO); fetal obstructive uropathy; trend analysis; antenatal diagnosis; pediatric urology